Nature-Based Solutions for Cities - McPhearson, Timon; Kabisch, Nadja; Frantzeskaki, Niki (Edward Elgar Publishing, 2023)
Nature-based solutions (NBS) are increasingly being adopted to address climate change, health, and urban sustainability, yet ensuring they are effective and inclusive remains a challenge. Addressing these challenges through chapters by leading experts in both global south and north contexts, this forward-looking book advances the science of NBS in cities and discusses the frontiers for next-generation urban NBS.